Juvenile phyllodes tumor of the breast - Prihantono; Bayu Satria; Muhammad Faruk (Journal of Pediatric Surgery Case Reports, 2020)
Introduction: Phyllodes tumor of the breast is a rare tumor in adolescents. Its incidence rate of 0,1% of all breast tumors in adolescents. Case presentation: We presented the case of a 19-year-old asian girls with a giant tumor of her right breast which rapidly enlarged in the last 3 months. Physical examination found 24cm tumor, tender, with altered contour and vein distension. Fine-needle aspiration biopsy (FNAB) showed benign phyllodes tumor. She was offered wide excision with resection margin 1 cm followed by McKissock mastopexy procedure. The treatment was well tolerated. No finding of recurrence on clinical and ultrasound examination at 1 year follow-up. Discussion: Phylloides is tumor of fibroepithelial origin mainly occurred in middle-aged women. Surgery is the primary treatment for phylloides tumor. Sufficient surgical margin reduces the risk of local recurrence. Mastectomy may become the preferred option for borderline, malignant or local tumor recurrence phylloides tumor. Post treatment follow-up needed to evaluate local recurrence and metastasis. Conclusion: Juvenile phylloides tumor is a rare breast neoplasm in adolescents. Wide excision with sufficient resection margins seems adequate treatment for phylloides tumor.